Method for determining cloth simulation filtering threshold value based on curvature value of fitting curve. (24th September 2021) - Sun, Jialong; Zhang, Zhengyang; Long, Bingxin; Qin, Siyuan; Yan, Yonghao; Wang, Lize; Qin, Jiangtao
Cloth Simulation Filtering (CSF) is an algorithm that is effectively applied to mobile 3D laser point cloud filtering. The classification threshold in cloth simulation is a key parameter for separating ground points and non-ground. The selection of classification threshold directly affects the point cloud filtering effect. In this paper, based on the filtering of the CSF algorithm, a method for calculating the threshold-filtering total error fitting curve curvature value to determine the cloth simulation classification threshold is proposed. First, according to the relationship between the classification threshold and filtering error in CSF, the least squares optimal fitting function is established; then calculate the curvature value of the fitted curve to determine the optimal classification threshold; finally, the final filtering errors of ground points and non-ground points are analysed by examples, and the effectiveness of this method in CSF filtering is verified, and a good filtering effect is obtained.